RELATIONSHIP BETWEEN BASAL PLASMA GLUCOSE LEVELS AND RECOVERING PROSPECTIVE OF PATIENTS WITH ACUTE STROKE - Popescu, Simona; Timar, Bogdan; Simu, Mihaela; Timar, Romulus (European Scientific Journal, ESJ, 2013)
﻿Introduction: Cardiovascular disease, especially coronary and cerebral, is the leading cause of death in diabetic patients. The aims of our study were to investigate carbohydrate metabolism disorders in patients with stroke, to analyze factors influencing stroke prognosis and to study the relationship between plasma glucose levels at admission and mortality rate after 14 days from the acute event in those patients. Materials and Method: For this study we enrolled 208 subjects diagnosed with stroke. For all subjects plasma glucose level at admission and after 14 days from admission was measured. We investigated the relationship between glycemia at admission and mortality rate respectively glycemia after 14 days. Results and discussion: From all patients involved in the study 31 had Type 2 Diabetes Mellitus (T2DM). In the patients group without previously diagnosed T2DM, 19 had plasma glucose level at admission > 125 mg/dL, 12 between 110-125 mg/dL and 146 below 110 mg/dL. In the group of patients not previously diagnosed with diabetes having plasma glucose level > 125 mg/dL at admission, 66.7% still had plasma glucose >125 mg/dL after 14 days from admission. We found a positive correlation between plasma glucose level at admission and mortality caused by stroke. Conclusions: T2DM is a major risk factor for stroke. Plasma glucose level at admission was correlated positively with stroke mortality, both in patients with T2DM and in those without previously diagnosed T2DM, independently of other related factors.